Study on Leaching Lanthanum From Ferronickel Slag With Pretreatment Alkaline Fusion - Yudomustafa, Fakhruddin; Febriana, Eni; Mayangsari, Wahyu; Ciptasari, Nurhayati Indah; Akbar, Ari Yustisia; Hendrik, Hendrik; Oediyani, Soesaptri; Prasetyo, Agus Budi (Metalurgi, 2024)
Ferronickel slag is a byproduct of nickel ore smelting. Several efforts have been made to find alternative applications for ferronickel slag, such as the production of construction materials, cement, or geopolymers. It is reported that 38% is used for road construction, 48% is used for industrial cement mixtures, and the rest is used for fertilizers, geopolymers, and hydraulic techniques. Ferronickel slag still contains some valuable minerals such as silica, magnesium, nickel, iron, and several REEs (rare earth elements). One of the REEs, namely lanthanum, has many applications, including Ni-MH (nickel-metal hydride) batteries, phosphors for lamps, fluid-cracking catalysts for oil refining, LaNi5 for hydrogen gas storage, metal alloys for cast iron, steel and magnesium alloys, additives for glassware (for cameras), and lanthanum hexaboride ceramic. In connection with the slag, which contains impurities in strong silica compounds, it is necessary to carry out an alkaline fusion treatment. Alkaline fusion was carried out by varying the time from 0.5 to 4 hours and the ratio of the mass of slag to NaOH: 1:0.6, 1:1, 1:1.23, 1:1.47, and 1:1.84. The biggest decrease in SiO2 was in the 3-hour alkaline fusion time, from 48.347% to 27.3%, and in the mass ratio at 1:1.47, from 48.347% to 21.413%. This research aims to provide added value for ferronickel slag by extracting lanthanum by acid leaching using H2SO4 reagent by varying the time (5, 10, 30, 60, and 120 minutes), temperature (30, 60, and 90 °C), and concentration (1, 2, and 3 M). The results showed that the best leaching point was at 5 minutes, 30 °C, and 1 M, yielding a lanthanum extraction percentage of 38.082%.